Age and sex differences in the impact of the COVID-19 pandemic on mental health and coping mechanisms in Latin American youth. (December 2022) - Ulloa, Rosa Elena; Apiquian, Rogelio; de la Peña, Francisco R.; Díaz, Ricardo; Mayer, Pablo; Palacio, Juan David; Palacios-Cruz, Lino; Hernández, Andrea; García, Pamela; Rosetti, Marcos F.
Abstract: Background: The COVID-19 pandemic has had negative effects on mental health. Understanding sex and age differences in the perception of stressors, the use of coping strategies, and the prevalence of depression and anxiety can lead to detecting at-risk groups. Methods: A cross-sectional online study surveyed perceived stressors, coping strategies, and the PHQ-9 and GAD-7 rating scales for symptoms of depression and anxiety. The study was open from Spring 2020 to Spring 2021 and was aimed at children, adolescents and young adults of Latin America. Results: The survey was completed by 3965 participants (63.8% females). The sample was divided into children (N = 621, 15.7%), adolescents (N = 1123, 28.3%) and young adults (N = 2021, 56%). Moderate to severe symptoms of depression and anxiety were found in 43.53% and 27%, respectively, being more frequent in females. Children of both sexes showed the lowest scores in rating scales. Adult females reported a higher level of stress in regards to pandemic news, having someone close diagnosed with COVID-19, the possibility of getting sick, academic delays, economic impact, and depression, while female adolescents reported a higher level of stress regarding the lockdown, losing contact with peers and anxiety. In juxtaposition, females also reported a higher frequency of positive coping strategies. A multivariate analysis confirmed the association of several variables with the presence of depression and anxiety. Conclusion: A high prevalence of depression and anxiety was found among young people. Specific intervention programs must be created taking into account age and sex differences.